Analysis of Employee Discipline in the Organization and Administration of the Regional Secretariat of Binjai City - Putri Salsa Nabila; M. Irwan Padli Nst (Penerbit Jurnal Indonesia, 2022)
This study aims to find out how the work discipline of employees in the organization and management section at the Regional Secretariat of Binjai City is. This research is the Regional Secretariat of Binjai City with a population of all employees in the organization and management section. The data collection technique used in this study was interviews with informants related to this research. Based on the results of the study, it was found that from the results of the research that the author has done in the Organization and Administration Section of the Binjai Regional Secretariat regarding employee work discipline that work discipline in this section is still not going well, this can be seen from the indicators used to see the program the work discipline of the employees of the Organization and Administration Section. These indicators are in the form of capabilities given to employees, examples of leaders who are not capable of providing/good examples for employees, lack of waskat (inherent supervision), inappropriate legal sanctions, firmness in providing work discipline guidance not in accordance with established regulations. , as well as less harmonious human relations